Effects of benzophenone-3 on the liver and thyroid of adult zebrafish - Medeiros da Silva, Felismário; Pena Modesto, Renan; Cávoli Lira, Mirelly Cândida; Libanio Reis Santos, Eduardo [UNESP]; Oliveira-Lima, Jeffesson de (Taylor & Francis, 2024)
Benzophenone-3 (BP-3), commonly known as oxybenzone, is an organic compound that acts as a sunscreen, protecting the skin from UVA and UVB rays. Thus, the objective of this study was to investigate the effects of BP-3 on the liver and thyroid using morphological and biochemical approaches. Adult male zebrafish were randomly assigned to three groups, each with three repetitions (n = 10 per group) water control, solvent control (0.01% ethanol), and 1 μg/L of BP-3, using a static exposure system for 96 h. After the experiment, histopathological analyses of the liver and thyroid were performed, along with histochemical analyses (glycogen) and biochemical evaluations of the antioxidant enzymes superoxide dismutase (SOD) and Catalase (CAT). Exposure to BP-3 resulted in significant histopathological changes in the liver of Danio rerio, increasing the frequency of circulatory disturbances, progressive changes, inflammatory responses, and regressive changes. On the other hand, the thyroid gland did not show any morphological changes during exposure to BP-3, maintaining its typical structure with follicles. There was a significant increase in SOD activity, while CAT showed no changes after 96 h of exposure. The results obtained demonstrate that exposure to BP-3 causes significant morphophysiological changes in the liver of D. rerio, highlighting not only the negative impacts on the health of these organisms but also the ecotoxicological potential of the substance and its consequences for aquatic biota in contaminated environments.
Keywords: benzophenone-3; Danio rerio; Ecotoxicology; histopathology; oxidative stress